A Comprehensive Antioxidant and Nutritional Profiling of Brassicaceae Microgreens - Anja Vučetić; Olja Šovljanski; Lato Pezo; Nevenka Gligorijević; Saša Kostić; Jelena Vulić; Jasna Čanadanović-Brunet (Antioxidants)
Microgreens are gaining prominence as nutrient-dense foods with health-promoting activities while aligning with smart agriculture and functional food trends. They are rich in numerous bioactive compounds like phenolics, ascorbic acid, and carotenoids, which act as antioxidants, while also causing multiple other biological activities. Using advanced statistical methods, this study investigated Brassicaceae microgreens, identifying kale and Sango radish as standout varieties. Both contained 16 amino acids, with potassium and calcium as dominant minerals. Sugar and protein contents ranged from 4.29 to 4.66% and 40.27 to 43.90%, respectively. Kale exhibited higher carotenoid levels, particularly lutein (996.36 mg/100 g) and beta-carotene (574.15 mg/100 g). In comparison, Sango radish excelled in glucose metabolism (α-glucosidase inhibition: 58%) and antioxidant activities (DPPH•: 7.92 mmol TE/100 g, ABTS•+: 43.47 mmol TE/100 g). Both showed antimicrobial activity against Escherichia coli and Staphylococcus aureus. Kale demonstrated stronger anti-inflammatory effects, while Sango radish showed antiproliferative potential. These results, supported by PCA and correlation analysis, underscore the dual role of these microgreens as nutritious and therapeutic food additives, addressing oxidative stress, inflammation, and microbial threats.